Prophylactic Effect of Mycobacterium bovis BCG Vaccination against Osteomyelitis in Children with Mycobacterium ulcerans Disease (Buruli Ulcer) - Portaels, F. (American Society for Microbiology, 2002)
Mycobacterium ulcerans disease, or Buruli ulcer (BU), causes significant morbidity in West Africa. In 233 consecutive, laboratory-confirmed samples from BU patients in Benin whose Mycobacterium bovis BCG scar status was known, 130 children (<15 years old) and 75 adults had a neonatal BCG vaccination scar. Of 130 children with BCG scars, 10 (7.7%) had osteomyelitis, while 3 of 9 children without BCG scars (33.3%) had osteomyelitis. Our observations support the conclusion that having a BCG vaccination scar provides significant protection against M. ulcerans osteomyelitis in children with BU disease.